TAFSIR GENDER DALAM TAFSÃ®R AL-MANÃ¢R TENTANG ASAL KEJADIAN PEREMPUAN - Bilqis Fajarwati, Ana (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
The Koran presents the topic of women in many verses and letters. But the most is in the letter al-Nisâ? so that he is often called al-Nisâ? al-Kubrâ. Although the Koran is the holy book of eternal truth, interpretation cannot be avoided as a relative. Historical development of various sect of kalâm, fiqh, and sufism is positive proof of the relativity of appreciation of religious Muslims. At one period, the levels of intellect into dominant, on the other period, the levels of emotionality become prominent. That is why the perception of women among Muslims, especially in self commentators, also varies from age to age the majority of Muslims are stuck with so many results ijtihâd of the scholars then regarded as a religion that cannot brain-tweaking and could not be bothered. But this fact does not actually like it. Therefore, this paper attempts to dismantle understanding of religious texts that have been used as legitimating for patriarchal mindset away from gender equality.